Mulheres na bíblia e na vida de Jesus: o caso de Marta e de Maria - Vieira, Maria das Graças (2010)
This research is an attempt to detect the true meaning and intention of Luke in the text that talks about Mary and Martha (Luke 10.38-42) and their connection with Jesus. I seek to analyze the situation of women in patriarchal society, their performance as they take care of the family and home and, at the same time, the audacity of the women who followed Jesus from Galilee to Jerusalem: how they served him, how they listened to him, how they risked their lives for him and assisted him up to the moment of his resurrection, spreading the news about the risen Lord. It is possible to perceive that, at all times, women have struggled for a decent life and gradually conquered their space and noticed that the human being, as a whole, needs reconciliation, female/male, recognizing the feminine values which were forgotten in androcentric societies. In various different contexts, many women began to participate actively in diverse movements, trade unions, grassroots communities, exercising a strong leadership, organizing biblical reflections and discovering that another world is possible.